Society in Manfaluti Innovative Literature - Farman Ullah Khan; Syed Abdul Salam Bacha (Journal of Islamic and Religious Studies, 2016)
This article describes the social problems face by the Egyptian people in the late nineteenth and beginning of twentieth century which are tackled by the writer Mu╖═afā Lu═fī Manfalū═ī in his articles and parables. In the mentioned period the Egyptian society was prone to immoralities carved by the English regime. Bad governance, deprivation of the Egyptian society from their basic rights, and negligence towards Islam were the major shortcomings on the part of the ruling elite. While poverty, problems of women, immorality, offence and other social evils were the main troubles on the part of Egyptian society. This article deals with the way the writer tackled those problems in his writings.